Influence of Nature Towards the Formation of Cosmology of Iban Community in Sarawak (Melayu: Jurnal Antarabangsa Dunia Melayu, 2025)
The Iban community has its own unique worldview in interpreting their beliefs about the world and life. The Iban community’s belief in the existence of the natural order is driven by the Pengarap Lama, which is the ancestral religious teachings that became the earliest platform shaping their thoughts at that time. This belief is closely related to the influence of nature, which moulds their cultural manifestations. Therefore, the purpose of this article aims to analyse the influence of nature in the formation of the Iban community’s cosmology in Sarawak. This study applies a qualitative approach in the form of ethnography through general observations, participant observations, and in-depth interviews with informants through collective memory techniques. The sampling of this study uses a non-probability sampling technique, where the informants recruited other informants they knew and had expertise related to the study. The study found that influence of nature plays a crucial role in shaping cosmology (the order of the universe) and helps the Iban community define their unique worldview. This study is hoped to serve as a reference for understanding the worldview of the Iban community in Sarawak and the formation of cosmology within the community. Full text: PDF